Collection 1988 : Marco Bagnoli - Dominique Blaise - Marinus Boezem - Marcel Broodthaers - Jean-Pierre Cluzel - Erik Dietman - Hans Hollein - Per Kirkeby - Sol LeWitt - Jaume Plensa - Alain Pouillet - René Roche - Hans van den Ban. - MAC, Musée d'Art Contemporain, Lyon (Lyon : Musée St. Pierre Art Contemporain, 1988)
Bagnoli, Marco ; Blaise, Dominique ; Boezem, Marinus ; Broodthaers, Marcel ; Cluzel, Jean-Pierre ; Dietman, Erik ; Hollein, Hans ; Kirkeby, Per ; LeWitt, Sol ; Plensa, Jaume ; Pouillet, Alain ; Roche, René ; van den Ban, Hans
Collection 1988 : Marco Bagnoli - Dominique Blaise - Marinus Boezem - Marcel Broodthaers - Jean-Pierre Cluzel - Erik Dietman - Hans Hollein - Per Kirkeby - Sol LeWitt - Jaume Plensa - Alain Pouillet - René Roche - Hans van den Ban, Musée St. Pierre Art Contemporain, Lyon, 29 janvier - 29 février 1988
boek